Correction to Phytotaxa 266: Replacement names for botanical taxa involving algal genera - Blanco, Saúl (Phytotaxa, 2016)
Recently Blanco & Wetzel (2016) proposed Williamriedelia Blanco & Wetzel (2016: 202) as a replacement name for Riedelia Jousé & Sheshukova-Poretzkaya (1971: 19). Hovever, Williamriedelia had been already used by Prema & Desikachary (2012) to solve the same homonymy, therefore the correct use of this name is hereby addressed.